Laminated film

JP2025024096AActive Publication Date: 2025-02-19ZACROS CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024199118
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-19
Estimated Expiration
2041-04-28

AI Technical Summary

Benefits of technology

【0016】 本発明の一態様は、表面抵抗値の上昇が起こりにくい表面保護フィルムおよび光学部品を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025024096000001_ABST
    Figure 2025024096000001_ABST
Patent Text Reader

Abstract

To provide a laminated film that is less susceptible to an increase in surface resistance value.SOLUTION: A laminated film 10 includes a substrate film 1 composed of a transparent resin and an antistatic agent layer 2 formed on one side of the substrate film 1. The antistatic agent layer 2 includes a first layer 2a containing a conductive polymer and a second layer 2b disposed on the side opposite to the substrate film 1 relative to the first layer 2a, the second layer 2b containing nanocarbon.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminated film. [Background technology]

[0002] When optical films such as polarizing plates, retardation plates, lens films for displays, anti-reflection films, hard coat films, transparent conductive films for touch panels, and other optical products such as displays using the same are manufactured and transported, a surface protective film is attached to the surface of the optical film to prevent the surface from being soiled or scratched in later processes. In order to improve work efficiency by eliminating the need to peel off the surface protective film and then reattach it, the appearance inspection of the optical film, which is a product, is sometimes performed with the surface protective film attached to the optical film.

[0003] Conventionally, a surface protection film having an adhesive layer on one side of a base film has been generally used in the manufacturing process of optical products to prevent scratches and dirt from adhering to the surface of the optical product. The surface protection film is attached to the optical film via an adhesive layer having a weak adhesive force. The adhesive layer has a weak adhesive force so that the used surface protection film can be easily peeled off when peeled off and removed from the surface of the optical film, and the adhesive does not adhere to and remain on the optical film of the product, which is the adherend (so-called, to prevent the occurrence of adhesive residue).

[0004] Surface protection films that have an antistatic layer on the opposite side of the adhesive layer of the base film are often used. By providing an antistatic layer on the surface of the surface protection film, static electricity that occurs during transportation and handling of the optical product to which the surface protection film is attached during the manufacturing process of the optical product is suppressed. This prevents the adhesion of dust and dirt in the environment and makes it easier to perform visual inspection of the surface protection film while it is attached to the optical film. In addition, when the surface protection film is peeled off from the polarizing plate or retardation plate built into the liquid crystal display panel after use, significant peeling static electricity is suppressed, which prevents damage to circuits such as driver ICs.

[0005] Proposals have been made for the antistatic layer on the surface of the surface protection film, such as layers containing various surfactants (nonionic, cationic, anionic, amphoteric surfactants) or polymers containing ionic groups, vapor deposition of metal or metal oxide, or layers containing metal or metal oxide particles. Antistatic layers containing surfactants or ionic group-containing polymers are susceptible to the effects of humidity in the environment, and have a high antistatic effect in high humidity environments, but have a problem that their antistatic performance deteriorates significantly in low humidity environments. On the other hand, antistatic layers containing metal or metal oxide particles are not susceptible to the effects of humidity in the environment, but are difficult to achieve transparency, and cannot be used for optical products, particularly for inspections with a surface protection film attached. Examples of antistatic layers that are not susceptible to the effects of humidity in the environment and have transparency include antistatic layers formed by vapor deposition of metal oxides such as indium tin oxide (ITO) and antimony tin oxide (ATO), but have a problem that the cost of vapor deposition is very high.

[0006] Patent Document 1 discloses a surface protection film in which an antistatic layer is provided on one side of a polyester film, an antifouling layer is provided on the antistatic layer, and a weak adhesive layer is provided on the opposite side. The antistatic layer contains a conductive polymer obtained by polymerizing thiophene and / or a thiophene derivative. However, when the antistatic layer is formed using the conductive polymer, there is a problem that problems such as an increase (deterioration) in surface resistivity due to oxidation degradation and photodegradation occur over time.

[0007] In order to solve this problem of surface resistivity increasing (deteriorating) over time, Patent Document 2 proposes a surface protection film in which an antistatic layer contains polyaniline sulfonic acid, polythiophenes doped with polyanions, and a binder. This surface protection film is said to be able to suppress the increase (deterioration) in surface resistivity over time by using polyaniline sulfonic acid in combination with the antistatic layer, but there is a risk of coloring from yellow to green due to the polyaniline, making it difficult to use for optical components.

[0008] Patent Document 3 describes an antistatic film having good transparency (total light transmittance) and good adhesion of the antistatic layer to a substrate, which further includes a conductive layer containing nanocarbon and a polymer, and the surface resistivity of the antistatic film is 1×10 11 An antistatic film with a surface resistance of Ω / □ or less has been proposed. However, because this antistatic film uses nanocarbons such as carbon nanotubes as an antistatic agent, the surface resistance increases only slightly over time, but there is an issue that the surface resistance increases (deteriorates) when placed in a humid and hot environment (for example, conditions of 60°C and relative humidity of 90%).

[0009] Patent Document 4 proposes a thermosetting antistatic coating agent containing polythiophene and a conductive filler. This thermosetting antistatic coating agent has little change in surface resistivity over time. However, this thermosetting antistatic coating agent has a problem in that the surface resistivity increases (deteriorates) when placed in a high-temperature, humid and hot condition (such as a temperature of 60°C and a relative humidity of 90%). [Prior art documents] [Patent documents]

[0010] [Patent Document 1] JP 2000-026817 A [Patent Document 2] Re-tabled publication No. 2018-012545 [Patent Document 3] JP 2012-166452 A [Patent Document 4] JP 2016-216714 A Summary of the Invention [Problem to be solved by the invention]

[0011] One aspect of the present invention has been made in view of the above circumstances, and an object of the present invention is to provide a laminate film in which an increase in surface resistance value is unlikely to occur. [Means for solving the problem]

[0012] One aspect of the present invention provides a surface protection film comprising a substrate film made of a transparent resin, an antistatic agent layer formed on one side of the substrate film, and an adhesive layer formed on the side of the substrate film opposite the antistatic agent layer, the antistatic agent layer comprising a first layer containing a conductive polymer, and a second layer containing nanocarbon and provided on the opposite side of the substrate film from the first layer.

[0013] The surface protection film may have a release film attached to the side of the pressure-sensitive adhesive layer opposite to the base film.

[0014] The pressure-sensitive adhesive layer is preferably made of an acrylic pressure-sensitive adhesive.

[0015] Another aspect of the present invention provides an optical component having the above-mentioned surface protection film attached thereto. Effect of the Invention

[0016] One aspect of the present invention can provide a surface protection film and an optical component in which an increase in surface resistance is unlikely to occur. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a cross-sectional view showing a surface protection film according to an embodiment. [Diagram 2] 1 is a cross-sectional view showing a surface protective film with a release film in which a release film is bonded to a surface protective film of an embodiment. [Diagram 3] FIG. 1 is a cross-sectional view showing one embodiment of an optical component according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, the present invention will be described in detail based on the embodiments. Fig. 1 is a cross-sectional view showing a surface protection film of an embodiment. As shown in Fig. 1, a surface protection film 10 according to the embodiment has an antistatic agent layer 2 formed on one surface (upper surface in Fig. 1) of a base film 1. A pressure-sensitive adhesive layer 3 is formed on the surface of the base film 1 opposite to the antistatic agent layer 2 (lower surface in Fig. 1).

[0019] [Base film] As the base film 1, a base film made of a resin having transparency and flexibility is used. This allows the appearance inspection of the optical component to be performed in a state where the surface protection film 10 is attached to the optical component as the adherend. The base film 1 used as the base film 1 is preferably a film (polyester film) made of polyester such as polyethylene terephthalate, polyethylene naphthalate, polyethylene isophthalate, polybutylene terephthalate, etc. In addition to polyester films, films made of other resins can also be used as long as they have the necessary strength and optical suitability. The base film 1 may be a non-stretched film, or a uniaxially or biaxially stretched film. In addition, the stretching ratio of the stretched film and the orientation angle in the axial direction formed by the crystallization of the stretched film may be controlled to a specific value.

[0020] "Transparent" means that the visible light transmittance calculated as the average value of the transmittance in the thickness direction in the entire wavelength range when measured within a measurement wavelength range of 380 nm to 780 nm is 50% or more (preferably 70% or more, more preferably 80% or more). The light transmittance can be measured in accordance with "Plastics - Determination of total light transmittance and total light reflectance" as specified in JIS K 7375:2008.

[0021] The thickness of the base film 1 is not particularly limited, but is preferably about 12 to 100 μm, and more preferably about 20 to 50 μm for ease of handling. If necessary, the surface of the base film 1 may be subjected to a treatment for improving adhesion, such as surface modification by corona discharge or application of an anchor coating agent.

[0022] [Antistatic agent layer] The antistatic agent layer 2 is configured by laminating a first layer 2a containing a conductive polymer and a second layer 2b containing nanocarbon in this order from the side of the base film 1. The second layer 2b is provided on the opposite side of the first layer 2a to the base film 1 (the upper side in FIG. 1).

[0023] A layer containing a conductive polymer may experience an increase in surface resistivity (deterioration) over time due to oxidative or photodegradation. However, in the surface protection film 10, a second layer 2b containing nanocarbon is provided on the surface of the first layer 2a (the side opposite the base film 1), thereby overcoming the problem of oxidative or photodegradation of the first layer 2a containing a conductive polymer.

[0024] A layer containing nanocarbon may experience an increase in surface resistance (deterioration) when placed in a humid and hot environment (e.g., conditions of 60°C and relative humidity of 90%), but in the surface protective film 10, the antistatic effect of the first layer 2a between the second layer 2b and the base film 1 overcomes the problem of deterioration of the second layer 2b in a humid and hot environment.

[0025] Examples of the conductive polymer used in the first layer 2a include polyaniline, polythiophene, polypyrrole, and derivatives thereof. Available examples of polyaniline and its derivatives include polyaniline (manufactured by Aldrich Corporation), polyaniline (eleraldine salt) (manufactured by Aldrich Corporation), OMEGACON (registered trademark) D1033W, OMEGACON (registered trademark) NW-D102MT, OMEGACON (registered trademark) NW-F102ET, OMEGACON (registered trademark) NW-F101MEK (all manufactured by Nissan Chemical Industries, Ltd.), Aquapass (registered trademark) 01X (manufactured by Mitsubishi Chemical Corporation), and polyaniline toluene solution PANT (manufactured by Kaken Sangyo Co., Ltd.).

[0026] Commercially available polythiophenes and derivatives thereof include 3,4-ethylenedioxythiophene (BAYTRON® MV2), 3,4-polyethylenedioxythiopene / polystyrenesulfonate (BAYTRON® P, BAYTRON® C), BAYTRON® FE, BAYTRON® MV2, BAYTRON® P, BAYTRON® PAG, BAYTRON® PHC V4, BAYTRON® PHS, BAYTRON® PH, and BAYTRON® PH500. , BAYTRON (registered trademark) PH510 (all manufactured by Starck), SEPLEGYDA (registered trademark) AS-Q, SEPLEGYDA (registered trademark) AS-D, SEPLEGYDA (registered trademark) AS-H (all manufactured by Shin-Etsu Polymer Co., Ltd.), Conductive Coat S-983, Conductive Coat S-495, Conductive Coat S-948 (all manufactured by Chukyo Yushi Co., Ltd.), Denatron P-502RG, Denatron P-560ST, Denatron P-500NT, Denatron P-200HC, Denatron P-800SL (all manufactured by Nagase Chemtec Corporation), PED500 (manufactured by Kaken Sangyo Co., Ltd.), and the like are available.

[0027] As polypyrrole and its derivatives, polypyrrole (manufactured by Aldrich Co.), SSPY (manufactured by Kaken Sangyo Co., Ltd.), and the like are available.

[0028] As the conductive polymer, polythiophene is preferable in terms of antistatic property and colorability (color). As the polythiophene, polyethyleneoxythiophene is preferable, and polyethylenedioxythiophene (PEDOT) is particularly good. Polyethylenedioxythiophene is preferably doped with polystyrene sulfonic acid (PSS) as a dopant. Polyethylenedioxythiophene doped with PSS has the advantages of being highly soluble in water and having excellent heat resistance, moisture resistance, and UV stability.

[0029] The conductive polymer may be used alone or in combination with a plurality of different types. For the purpose of improving the applicability of the antistatic agent to the base film 1, the adhesion of the antistatic agent layer to the base film, the film strength of the antistatic agent layer, and the durability of the film (such as abrasion resistance and solvent resistance), a binder resin, a crosslinking agent, an ultraviolet absorber, an antioxidant, a leveling agent (wettability improver), an adhesion improver, and the like may be added to the conductive polymer.

[0030] To form the first layer 2a, it is preferable to form a film of a conductive polymer to which a binder resin has been added, rather than forming a film of a conductive polymer alone. Examples of binder resins include acrylic resins, epoxy resins, urethane resins, phenolic resins, and polyester resins. If necessary, a crosslinking agent may be added to the binder resin in order to crosslink (also called harden) these resins. Examples of crosslinking agents include isocyanate compounds, melamine compounds, epoxy compounds, and metal chelate compounds.

[0031] The method for forming the first layer 2a on the base film 1 may be a known method. For example, a paint containing an antistatic agent (a paint containing an antistatic agent and a binder resin) is applied to the base film 1 by a known coating method. The first layer 2a can be formed by solidifying the formed coating film by heating or irradiating with ultraviolet light. Examples of the coating method include reverse coating, comma coating, gravure coating, slot die coating, Mayer bar coating, and air knife coating.

[0032] Examples of nanocarbons used in the second layer 2b include carbon nanotubes (CNTs), graphene, and fullerenes. Carbon nanotubes include single-walled CNTs and multi-walled CNTs. Single-walled CNTs, multi-walled CNTs, graphene, and fullerenes all have excellent antistatic properties, but since single-walled CNTs, graphene, and fullerenes are expensive, multi-walled CNTs are easier to use. The second layer 2b is formed on the surface of the first layer 2a to prevent the first layer 2a from being exposed to air. As a result, the first layer 2a is not directly exposed to air, making the first layer 2a less susceptible to oxidation deterioration.

[0033] Nanocarbon alone does not provide sufficient film strength, so it is preferable to add a binder resin, a dispersant, etc. to form a coating material for use. In addition, a crosslinking agent, an ultraviolet absorber, an antioxidant, a leveling agent (wettability improver), an adhesion improver, etc. may be added to the nanocarbon for the purpose of improving the coatability of the antistatic agent, the adhesion of the antistatic agent layer (adhesion to the first layer 2a), the film strength of the antistatic agent layer, and the durability of the film (abrasion resistance, solvent resistance, etc.).

[0034] Nanocarbon may be used alone or in combination with a plurality of types. Examples of binder resins include acrylic resins, epoxy resins, urethane resins, phenolic resins, and polyester resins. If necessary, a crosslinking agent may be added to the binder resin to crosslink (also called harden) these resins. Examples of crosslinking agents include isocyanate compounds, melamine compounds, epoxy compounds, and metal chelate compounds.

[0035] To form the second layer 2b, a commercially available antistatic paint may be used, such as Denatron C-300, Denatron CD-001 (both manufactured by Nagase Chemtec Corporation), Colcoat CS-3002, and Colcoat CS-3202 (both manufactured by Colcoat Co., Ltd.).

[0036] The method for forming the second layer 2b on the surface of the first layer 2a may be a known method. For example, a paint containing nanocarbon (a paint containing nanocarbon and a binder resin) is applied to the surface of the first layer 2a using a known coating method. The formed coating film is solidified by heating or ultraviolet irradiation to form the second layer 2b. Examples of the coating method include reverse coating, comma coating, gravure coating, slot die coating, Mayer bar coating, and air knife coating.

[0037] The thicknesses of the first layer 2a and the second layer 2b are not particularly limited. The thickness of the first layer 2a is determined by the amount of conductive polymer and binder resin. The thickness of the second layer 2b is determined by the amount of nanocarbon and binder resin. The thicknesses of the first layer 2a and the second layer 2b are determined so that the surface resistivity is 10 to the power of 7 (10 7 ) ~ 10 to the power of 9 (10 9 ) should be adjusted accordingly.

[0038] [Adhesive layer] The adhesive layer 3 preferably has the properties of adhering to the surface of the adherend, being easily peelable after use, and not easily contaminating the adherend. Examples of adhesives used in the adhesive layer 3 include acrylic adhesives, urethane adhesives, and rubber adhesives. Adhesive resins such as polyethylene vinyl acetate resin can also be used as the adhesive. Of these, acrylic adhesives and urethane adhesives are particularly preferred.

[0039] The acrylic adhesive is preferably an adhesive obtained by adding a crosslinking agent to a (meth)acrylic polymer (acrylic resin composition). The meth)acrylic polymer is preferably a polymer obtained by copolymerizing a main monomer such as n-butyl acrylate, 2-ethylhexyl acrylate, isooctyl acrylate, isononyl acrylate, etc., a comonomer such as acrylonitrile, vinyl acetate, methyl methacrylate, ethyl acrylate, etc., and a functional monomer such as acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxybutyl acrylate, glycidyl methacrylate, N-methylol methacrylamide, etc. The monomer composition constituting the (meth)acrylic polymer is preferably 50% or more of (meth)acrylic monomer, and may be 100% of (meth)acrylic monomer.

[0040] The crosslinking agent crosslinks the (meth)acrylic polymer. Examples of the crosslinking agent include an isocyanate compound, an epoxy compound, a melamine compound, and a metal chelate compound. The amount of the crosslinking agent to be added may be determined in consideration of the type of the (meth)acrylic polymer, the degree of polymerization, the amount of functional groups, and the like. The amount of the crosslinking agent to be added is not particularly limited, but is preferably about 0.5 to 1.0 parts by mass of the crosslinking agent per 100 parts by mass of the (meth)acrylic polymer.

[0041] The urethane-based adhesive is preferably a polyurethane-based resin containing a polyol component and a polyisocyanate component. The polyurethane-based resin may be selected in consideration of adhesion, wettability, adherend contamination, etc. The polyol component and the polyisocyanate component are not particularly limited. The polyurethane-based resin may be used alone or in combination of two or more kinds.

[0042] Examples of the polyol component include polyester polyol, polyether polyol, polycaprolactone polyol, polycarbonate polyol, castor oil polyol, etc. These polyol components may be used alone or in combination of two or more.

[0043] The polyisocyanate component may be an aliphatic polyisocyanate, an alicyclic polyisocyanate, an aromatic polyisocyanate, a diisocyanate polymer, etc. These polyisocyanate components may be used alone or in combination of two or more.

[0044] Commercially available polyurethane adhesives include Cyabain (registered trademark) SH-101, SH-101M, SP-205, and SP-220 (manufactured by Toyochem Co., Ltd.), Aracoat (registered trademark) FT100 and FT200 (manufactured by Arakawa Chemical Industries, Ltd.), UN1175, and UN1176 (manufactured by Daido Chemical Industry Co., Ltd.), etc. The adhesive layer may be formed by crosslinking or curing a polyurethane adhesive.

[0045] If necessary, a crosslinking catalyst may be added as an additive to the pressure-sensitive adhesive layer 3 in order to promote a crosslinking reaction. If necessary, an adhesion improver such as a silane coupling agent may be added as an additive to the pressure-sensitive adhesive layer 3 in order to improve the adhesion between the base film 1 and the pressure-sensitive adhesive. If necessary, additives such as an antistatic agent, an antioxidant, and an ultraviolet absorbing agent may be added to the pressure-sensitive adhesive layer 3.

[0046] The thickness of the adhesive layer 3 is not particularly limited, but is preferably about 5 to 40 μm, and more preferably about 10 to 30 μm. The adhesive strength of the surface protection film to the surface of the adherend at a peeling speed of 0.3 m / min (low-speed adhesive strength) is preferably 0.3 N / 25 mm or less, and more preferably 0.2 N / 25 mm or less. The adhesive strength at a peeling speed of 30 m / min (high-speed adhesive strength) is preferably 0.8 N / 25 mm or less. If the high-speed adhesive strength exceeds 0.8 N / 25 mm, the workability when peeling off the protective film after use may be deteriorated. The adhesive strength can be adjusted by known methods such as changing the adhesive composition, adjusting the amount of curing agent added, and adjusting the amount of tackifier or adhesive strength adjuster added. By these methods, the adhesive strength of the adhesive layer 3 can be adjusted to a predetermined adhesive strength.

[0047] A known method can be used to form the pressure-sensitive adhesive layer 3 on the surface of the base film 1. Specifically, known coating methods such as reverse coating, comma coating, gravure coating, slot die coating, Mayer bar coating, and air knife coating can be used.

[0048] FIG. 2 is a cross-sectional view showing a surface protection film 11 with a release film 4 attached to a surface protection film 10. As shown in FIG. 2, a known release film may be used as the release film 4. As the release film 4, a polyolefin film such as a polyethylene film or a polypropylene film, or a fluorine film may be used alone. The release film 4 may be a release film obtained by treating a resin film with a release agent (also called a release agent). Examples of the resin film include polyester films such as PET (polyethylene terephthalate) and PEN (polyethylene naphthalate), and polyamide films. Examples of the release agent include silicone resins, long-chain alkyl group-containing resins, and fluorine resins. Among them, a release film obtained by treating a PET film with a silicone-based release agent is preferable. The thickness of the release film is not particularly limited, but from the standpoint of workability and cost, a release film having a thickness of 12 to 38 μm is often used.

[0049] The method for forming the adhesive layer 3 on the base film 1 and the method for laminating the release film 4 to the adhesive layer 3 may be performed by a known method and are not particularly limited. Specifically, examples of the method include (1) a method in which a resin composition for forming the adhesive layer 3 is applied to one side of the base film 1, dried to form the adhesive layer 3, and then the release film 4 is laminated to the adhesive layer 3, and (2) a method in which a resin composition for forming the adhesive layer 3 is applied to the surface of the release film 4, dried to form the adhesive layer 3, and then the base film 1 is laminated to the adhesive layer 3, and any of these methods may be used.

[0050] Fig. 3 is a cross-sectional view showing an embodiment of an optical component of the present invention. Fig. 3 shows an optical component 20 to which a surface protection film 10 is attached. As shown in Fig. 3, a surface protection film 11 with a release film (see Fig. 2) is in a state in which the release film 4 has been peeled off to expose the pressure-sensitive adhesive layer 3. This surface protection film (see Fig. 1) is attached to an optical component 5, which is an adherend, by the pressure-sensitive adhesive layer 3.

[0051] Examples of the optical components include optical films such as a polarizing plate, a retardation plate, a lens film, a polarizing plate that also serves as a retardation plate, and a polarizing plate that also serves as a lens film. Such optical components are used as components of liquid crystal display devices such as liquid crystal display panels, optical devices of various instruments, etc. Examples of the optical components also include optical films such as anti-reflection films, hard coat films, and transparent conductive films for touch panels.

[0052] According to the optical component of the embodiment, when the surface protection film is attached to the optical component (film for optical use) as an adherend, an antistatic agent layer is present on the surface of the surface protection film. Therefore, it is possible to suppress static electricity generated during transportation or handling of the optical component. Therefore, it is possible to suppress the adsorption of substances that cause foreign matter such as dust and dirt during the process, and to obtain optical components with fewer defects. In addition, when the surface protection film is peeled off and removed from the optical component, it is possible to suppress the peeling electrification voltage to be low, so that there is little risk of damaging circuit components such as driver ICs, TFT elements, and gate line driving circuits. Therefore, for example, it is possible to increase the production efficiency in the process of manufacturing liquid crystal display panels and the like, and maintain the reliability of the production process. The surface protection film of the embodiment can suppress an increase (deterioration) in the surface resistance value of the antistatic agent layer on the surface even when exposed to outdoor air or in a humid and hot environment, and the above-mentioned effects are unlikely to change over time, so that the surface protection film has great industrial utility. EXAMPLES

[0053] The present invention will now be further described with reference to examples. Example 1 As an antistatic agent composition containing a conductive polymer, an antistatic agent A was prepared which contained a polythiophene-based antistatic agent (BAYTRON (registered trademark) PAG manufactured by Starck), an acrylic resin (PESRESIN (registered trademark) SWX-079R manufactured by Takamatsu Oil Co., Ltd.), and a methylated melamine crosslinking agent (NIKALAC (registered trademark) MW-30HM manufactured by Nippon Carbide Industries Co., Ltd.) in a solid content mass ratio of 30 / 100 / 10.

[0054] As an antistatic agent composition containing nanocarbon, antistatic agent B was prepared which contained a carbon nanotube dispersion (Denatron (registered trademark) CD-100 manufactured by Nagase ChemteX Corporation), an acrylic resin (PESRESIN (registered trademark) SWX-079R manufactured by Takamatsu Oil Co., Ltd.), and a methylated melamine crosslinking agent (NIKALAC (registered trademark) MW-30HM manufactured by Nippon Carbide Industries Co., Ltd.) in a solid mass ratio of 10 / 100 / 10.

[0055] An adhesive consisting of a copolymer of 80 parts by mass of 2-ethylhexyl acrylate, 10 parts by mass of butyl acrylate, 7 parts by mass of methoxypolyethylene glycol (400) methacrylate, and 3 parts by mass of 2-hydroxyethyl acrylate was prepared. This adhesive is an acrylic adhesive. To 100 parts by mass of a 40% ethyl acetate solution of this adhesive, 0.3 parts by mass of lithium bis(trifluoromethanesulfonyl)imide as an antistatic agent and 2 parts by mass of "Coronate (registered trademark) HX manufactured by Tosoh Corporation" as an isocyanate curing agent were added, and the mixture was stirred and mixed to obtain adhesive composition 1.

[0056] The antistatic agent A was diluted 10 times with water / ethanol (mass ratio of water / ethanol: 50 / 50) to obtain a first coating material. The first coating material was applied to the surface of a 38 μm-thick polyethylene terephthalate film (PET film, base film) so that the thickness after drying was 0.15 μm, and dried for 1 minute in a hot air circulating oven at 120° C. This formed a first layer.

[0057] The antistatic agent B was diluted 10 times with water / ethanol (mass ratio of water / ethanol: 50 / 50) to obtain a second coating material. The second coating material was applied to the surface of the first layer so that the thickness after drying was 0.05 μm, and dried for 1 minute in a hot air circulating oven at 120° C. This formed the second layer. Through the above steps, an antistatic film was obtained in which the base film (PET film) / first layer (antistatic agent A) / second layer (antistatic agent B) were laminated in this order.

[0058] On the surface of the PET film on which the antistatic agent layer was not laminated, the pressure-sensitive adhesive composition 1 was applied using an applicator so that the thickness after drying would be 20 μm, and the applied coating was dried for 3 minutes in a hot air circulating oven at 120° C. Thus, a pressure-sensitive adhesive layer was formed.

[0059] A release film (25 μm thick) (Diafoil (registered trademark) MRF-25 manufactured by Mitsubishi Chemical Corporation) treated with a silicone-based release agent was attached to the surface of the adhesive layer to obtain a surface protection film with a release film. The obtained surface protection film with the release film was aged at 40° C. for 3 days to obtain the surface protection film of Example 1.

[0060] Example 2 A surface protective film of Example 2 was produced in the same manner as in Example 1, except that the thicknesses of the first layer and the second layer were both 0.1 μm.

[0061] Example 3 A surface protective film of Example 3 was produced in the same manner as in Example 1, except that the thickness of the first layer was 0.05 μm and the thickness of the second layer was 0.15 μm.

[0062] Example 4 A surface protective film of Example 4 was produced in the same manner as in Example 2, except for the adhesive and curing agent. As the adhesive, a urethane adhesive (Arakawa Chemical Industries, Ltd., Alacoat (registered trademark) FT200) was used instead of an acrylic adhesive. As the hardener, 5.7 parts by mass of "Arakawa Chemical Industries, Ltd., Alacoat (registered trademark) CL2503 (hardener non-volatile content is 40% by mass)" was used instead of 2 parts by mass of "Tosoh Corporation, Coronate (registered trademark) HX."

[0063] Example 5 The surface protection film of Example 5 was prepared in the same manner as Example 2, except that a polyester resin (Vylonal (registered trademark) MD-1480 manufactured by Toyobo) was used instead of the acrylic resin (Pesresin (registered trademark) SWX-079R manufactured by Takamatsu Oil Co., Ltd.).

[0064] Comparative Example 1 A surface protection film of Comparative Example 1 was obtained in the same manner as in Example 1, except that the thickness of the first layer was 0.2 μm and that there was no second layer.

[0065] Comparative Example 2 A surface protection film of Comparative Example 2 was obtained in the same manner as in Example 1, except that the first layer was not present and the thickness of the second layer was set to 0.2 μm.

[0066] Comparative Example 3 A surface protection film of Comparative Example 3 was produced in the same manner as in Example 2, except that an antistatic agent layer of a single layer structure was used instead of the antistatic agent layer of a two-layer structure. The single-layer antistatic agent layer was formed by coating an antistatic agent prepared by mixing antistatic agent A and antistatic agent B in a solid content mass ratio of 50 / 50 so as to have a thickness of 0.2 μm after drying.

[0067] Comparative Example 4 A surface protection film of Comparative Example 4 was obtained in the same manner as in Example 2, except that the positions of the first layer and the second layer were reversed.

[0068] Comparative Example 5 A surface protection film of Comparative Example 5 was produced in the same manner as in Example 1, except that the first layer and the second layer were not included.

[0069] The evaluation test methods and results are shown below. (Method for measuring the surface resistivity of surface protection film) The surface resistivity (Ω / □) of the surface protective film was measured using a high-performance resistivity meter (Hiresta (registered trademark)-UP manufactured by Mitsubishi Chemical Analytech Co., Ltd.) under conditions of an applied voltage of 100 V and a measurement time of 30 seconds.

[0070] (Method of evaluating resistance to moist heat) The surface protection film was left for a predetermined period (1 day or 30 days) under conditions of a temperature of 60°C and a relative humidity of 90%, and then left for 1 hour under conditions of a temperature of 23°C and a relative humidity of 50%. The surface resistivity (Ω / □) of the surface protection film was measured using a high-performance high resistivity meter (Hiresta (registered trademark)-UP manufactured by Mitsubishi Chemical Analytech Co., Ltd.) under conditions of an applied voltage of 100 V and a measurement time of 30 seconds.

[0071] (Exposure resistance evaluation method) The surface protection film was left exposed to air at a temperature of 23°C and a relative humidity of 50% for a predetermined period of time (1 day or 30 days). The surface resistivity (Ω / □) of the surface protection film was measured using a high-performance resistivity meter (Hiresta (registered trademark)-UP manufactured by Mitsubishi Chemical Analytech Co., Ltd.) at an applied voltage of 100 V and a measurement time of 30 seconds.

[0072] <Method for measuring low speed adhesive strength of surface protection film> A polarizing plate using a TAC film as a polarizer protective film was laminated to the surface of a glass plate using a laminating machine. Then, a surface protective film cut to a width of 25 mm was laminated to the surface of the polarizing plate, and the plate was stored for one day under a test environment of 23°C x 50% RH. Then, the strength was measured when the surface protective film was peeled off in the 180° direction at a peeling speed of 0.3 m / min using a tensile tester, and this was taken as the low-speed adhesive strength (N / 25 mm).

[0073] <Method for measuring high-speed adhesive strength of surface protection film> A polarizing plate using a TAC film as a polarizer protective film was laminated to the surface of a glass plate using a laminating machine. Then, a surface protective film cut to a width of 25 mm was laminated to the surface of the polarizing plate, and the plate was stored for one day under a test environment of 23°C x 50% RH. Then, a high-speed peel tester (manufactured by Tester Sangyo) was used to measure the strength when the surface protective film was peeled off at a peeling speed of 30 m per minute, and this was taken as the high-speed adhesive strength (N / 25 mm).

[0074] <Method for measuring the peeling electrification voltage of surface protection film> A polarizing plate using a TAC film as a polarizer protective film was laminated on the surface of a glass plate using a laminating machine. After that, a surface protective film cut to a width of 25 mm was laminated on the surface of the polarizing plate, and then the polarizing plate was stored for one day under a test environment of 23°C x 50% RH. Then, the surface protective film was peeled off at a peeling speed of 30 m per minute using a high-speed peeling tester (manufactured by Tester Sangyo Co., Ltd.), and the surface potential of the polarizing plate surface was measured every 10 ms using a surface potential meter (manufactured by Keyence Corporation). The maximum absolute value of the surface potential was taken as the peeling electrification voltage (kV).

[0075] <Method for checking surface contamination of surface protection film> A polarizing plate using a TAC film as a polarizer protective film was laminated on the surface of a glass plate using a laminating machine. Then, a surface protective film cut to a width of 25 mm was laminated on the surface of the polarizing plate, and the plate was stored for 3 days under a test environment of 23°C x 50% RH. The surface protective film was then peeled off, and the surface contamination of the polarizing plate was visually observed. As the criterion for judging the surface contamination, a case where there was no contamination transfer to the polarizing plate was rated as "○" (Good), and a case where contamination transfer was confirmed to the polarizing plate was rated as "×" (No Good).

[0076] The measurement results for the surface protection films of Examples 1 to 5 and Comparative Examples 1 to 5 are shown in Tables 1 to 3. In Tables 1 to 3, "CNT" indicates the ratio of the thickness of the second layer to the total thickness of the first layer and the second layer. "PEDOT" indicates the ratio of the thickness of the first layer to the total thickness of the first layer and the second layer. "CNT / PEDOT (Mix)" indicates the mixing ratio of antistatic agent B and antistatic agent A in the antistatic agent (mixture) when an antistatic agent layer with a single layer structure is used. "100 (50 / 50)" means that the solid mass ratio of antistatic agent A and antistatic agent B is both 50%.

[0077] "Antistatic agent layer stacking order reversed" indicates the stacking order of the first layer and the second layer. "◯" indicates that the stacking order of the base film, the first layer, and the second layer is "base film / second layer / first layer." The "◯" next to "acrylic resin" indicates that the binder resin in the first and second layers is an acrylic resin. The "◯" next to "polyester resin" indicates that the binder resin in the first and second layers is a polyester resin. An "○" for "acrylic adhesive" indicates that an acrylic adhesive was used as the adhesive. An "○" for "urethane adhesive" indicates that a urethane adhesive was used as the adhesive. A surface resistivity value of 1.0E+09 represents 1.0 x 10 to the power of 9. 1.0E+13< represents an over-range value that exceeds the measurement limit (1.0 x 10 to the power of 13) of the measuring device (high-performance high resistivity meter).

[0078] [Table 1]

[0079] [Table 2]

[0080] [Table 3]

[0081] The measurement results shown in Tables 1 to 3 reveal the following. In the surface protection films of Examples 1 to 5, the surface resistance value of the antistatic agent layer did not increase (deteriorate) even when exposed to the outside air and in a moist and hot environment. On the other hand, in Comparative Example 1 in which the antistatic agent layer was formed only with the first layer (containing a conductive polymer), an increase (deterioration) in the surface resistance value of the antistatic agent layer was observed when exposed to the outside air. In Comparative Example 2 in which the antistatic agent layer was formed only with the second layer (containing nanocarbon), an increase (deterioration) in the surface resistance value of the antistatic agent layer on the surface was observed in a humid and hot environment. In Comparative Example 3, in which the antistatic agent layer had a single-layer structure made of a mixture of antistatic agents A and B instead of a two-layer structure, the surface resistance value of the antistatic agent layer increased (degraded) slightly in a humid and hot environment. In an outdoor exposure environment, the surface resistance value of the antistatic agent layer on the surface increased (degraded) significantly. In Comparative Example 4, in which the order of laminating the antistatic agent layers was reversed from that in Examples 1 to 5, an increase (deterioration) in the surface resistance value of the antistatic agent layer on the surface was observed in an environment exposed to outdoor air and in a moist and hot environment. In Comparative Example 5, in which no antistatic agent layer was provided, it is presumed that static electricity is easily generated during the process because the surface resistivity of the surface protection film is high. [Industrial Applicability]

[0082] The surface protective film of the embodiment can be used to protect the surface of optical components, for example, in the production process of optical films such as polarizing plates, retardation plates, lens films, and various other optical components. The surface protective film of the embodiment can suppress the increase (deterioration) of the surface resistance value of the antistatic agent layer on the surface even when exposed to the outside air or in a humid and hot environment. The surface protective film of the embodiment can suppress static electricity generated during transportation or handling of an optical product to which the surface protective film is attached in the production process of an optical product, thereby reducing the adsorption of dust and dirt in the environment. The surface protective film of the embodiment can suppress significant peeling electrification when peeling and removing the surface protective film after use from a polarizing plate or retardation plate incorporated in a liquid crystal display panel, so there is little risk of damaging circuits such as driver ICs. Therefore, the yield of the production process can be improved, and the industrial utility value is great. [Explanation of symbols]

[0083] Reference Signs List 1...base film, 2...antistatic agent layer, 2a...first layer, 2b...second layer, 3...adhesive layer, 4...release film, 5...adherend (optical component), 10...surface protective film, 11...surface protective film with release film, 20...optical component.

Claims

1. A substrate film made of a transparent resin; an antistatic agent layer formed on one surface of the base film; Equipped with The antistatic agent layer is a first layer comprising a conductive polymer; a second layer including nanocarbon and disposed on the opposite side of the first layer from the base film; A laminated film comprising:

2. The conductive polymer is at least one selected from polyaniline, polythiophene, polypyrrole, and derivatives thereof. The laminated film according to claim 1 .

3. The nanocarbon is at least one selected from carbon nanotubes (CNTs), graphene, and fullerenes. The laminated film according to claim 1 or 2.

Citation Information

Patent Citations

  • Transparent electrode and method for producing transparent electrode

    WO2009060717A1

  • Surface-protective film

    JP2000026817A

  • Antistatic film

    JP2012166452A

  • Thermosetting antistatic coating agent, cured coating, and plastic film

    JP2016216714A